Different formulations of peracetic acid: effects on smear layer removal, dentine erosion, cytotoxicity and antibiofilm activity - Kennia Scapin Viola; Hernán Coaguila-Llerena; Elisandra Marcia Rodrigues; Cíntia Silva Santos; Gisselle Moraima Chávez-Andrade; Miriam Graziele Magro; Mario Tanomaru-Filho; Juliane Maria Guerreiro-Tanomaru; Gisele Faria (Journal of Applied Oral Science, 2022)
Abstract Objective: To assess the effects of different peracetic acid (PAA) formulations on smear layer (SL) removal, dentine erosion, cytotoxicity, and antibiofilm activity. Methodology: SL removal and dentine erosion were assessed using 90 premolars, distributed into six groups, according to final irrigation: PAA formulations (1% Sigma, 1% Bacterend OX, 1% Arposept, and 0.09-0.15% Anioxyde), 17% ethylenediaminetetraacetic acid (EDTA), and water (control). Cytotoxicity was assessed by methyl-thiazol-tetrazolium (MTT) and neutral red assays. Antibacterial and antibiofilm effectiveness was evaluated against Enterococcus faecalis. For cytotoxicity and antibiofilm activity assessment, the 2.5% NaOCl was also included. Results: EDTA, Sigma, and Bacterend OX removed more SL than Arposept, Anioxyde, and water (p<0.05). EDTA caused more severe dentine erosion than Sigma and Bacterend OX (p<0.05). Sigma and Bacterend OX had higher cytotoxicity than the other solutions (p<0.05). NaOCl, Bacterend OX, Sigma, and Anioxyde significantly reduced E. faecalis colony-forming units (CFU) (p<0.05). The 2.5% NaOCl solution promoted greater biofilm biomass reduction (p<0.05) than the other solutions. All PAA formulations promoted greater biomass reduction than 17% EDTA (p<0.05). Conclusions: Although Sigma and Bacterend OX had higher cytotoxicity, they had a SL removal capability similar to that of EDTA, were as effective as NaOCl against E. faecalis biofilm, and promoted less dentine erosion than EDTA. Arposept and Anioxyde failed to remove the SL, had lower cytotoxicity, and showed less bacterial activity than NaOCl.